THE EFFECT OF PRICE FLUCTUATIONS AND SALES PROMOTION ON REPEAT USAGE OF GOLD INSTALLMENT PRODUCTS AT BSI KC MADIUN AGUS SALIM - Zaind, Lauh Mahfudha (Ar-Rihlah : Jurnal Keuangan dan Perbankan Syariah, 2026)
This study was conducted at Bank Syariah Indonesia Madiun Branch Office and aims to examine the effect of gold price fluctuations and sales promotion on repeat usage of the gold installment product. The type of research method used is quantitative. The population in this study consists of gold installment customers at BSI Madiun Branch, with the sampling technique using nonprobability sampling, namely saturated sampling. Data were collected through questionnaires. To test and analyze the data, validity and reliability tests, classical assumption tests, regression analysis, coefficient of determination, and hypothesis testing were employed. The results of this study indicate that gold price fluctuations (X1) and promotion (X2) have a partial and significant effect on repeat usage (Y) in the gold installment product.